Health behaviour of patients with unstable angina pectoris - Monika Bieniak; Robert Jan Łuczyk; Mariusz Wysokiński; Wiesław Fidecki (Kazimierz Wielki University, 2018)
Abstract Introduction. The illnesses of the cardiovascular system are the biggest cause of death in Poland [9,10]. Unstable angina pectoris is the most frequently occurring manifestation of the acute coronary syndrome (ACS). It aggravates the severity of the course of ischaemic heart disease (IHD) and hence constitutes a direct threat to the life and health of the patient. Therefore, it seems well-based to encourage pro-healthy behaviour among patients with this disease [2,3,15]. The aim of the study. The aim of the study was to evaluate health behaviour of patients with unstable angina pectoris. Material and method. The study was conducted from November of 2016 to February of 2017 in three hospitals in Lublin among 194 patients with unstable angina pectoris. In the study the diagnostic survey method alongside with polling technique was utilised. The research reference consisted of Inventory of The Health Behaviour (Inwentarz Zachowań Zdrowotnych, IZZ) and the authorial methodology. Results. Patients with unstable angina pectoris described their health behaviour as 'average'. The patients' age, gender, level of education and place of residence influenced their health behaviour. The highest ratings were in the 61-70 years old category. A higher level of health behaviour was presented by women. The lowest ratings of health behaviour were given by patients with primary education. The ratings of health behaviour were higher among the inhabitants of urban areas. Keywords: health behaviour, ischaemic heart disease, unstable angina pectoris